Saving the Earth with Physics: The Important Role of Science in Overcoming the Climate Crisis - Arisa, Riris; Chusni, Muhammad Minan (Universitas Lambung Mangkurat, 2024)
Global warming is one of the most pressing issues of modern times. Rising Earth temperatures have serious consequences for life on Earth. Physics plays an important role in fighting global warming with various principles and applications. This article discusses physics's important role in overcoming the climate crisis and building a more sustainable future. The method used in this research is a literature review, which collects and analyzes various reliable sources, such as scientific journals, research reports, and mass media articles relevant to global warming and physical science. Where the journals used as references for obtaining data were 15 journals consisting of national and international journals. The article's content includes understanding the mechanisms of global warming through physical principles, developing renewable energy technology, increasing energy efficiency, mitigating the impacts of global warming, and increasing public awareness. Understanding the causes and effects of the climate catastrophe and creating ways to deal with it depends heavily on the physical sciences. Understanding the climate system and creating innovative technology to assist in lowering greenhouse gas emissions are two areas in which physicists have made significant strides. Still, much work needs to be done. Physicists must keep working to advance our knowledge of the climate system and create more cost-effective and efficient technology. Physicists should also support effective policy action and try to increase public knowledge of the climate crisis. Physicists can help create a more sustainable and ecologically friendly future for our world by continuing to create new knowledge and technology. The scope of their research was found to have numerous limitations by this investigation.